2007
DOI: 10.2514/1.21103
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Model of the Hollow Cathode Using Numerically Simulated Plasma Fluxes

Abstract: The first results from a hollow cathode thermal model are presented. The thermal model uses the spatially distributed plasma fluxes, calculated by a two-dimensional axisymmetric model of the plasma inside the emitter region, as the heat source to predict the hollow cathode and insert temperatures. The computed insert temperature profiles are compared with measured values for a cathode similar to the 0.635-cm diameter discharge cathode used in the NASA solar electric propulsion technology applications readiness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 17 publications
2
38
0
Order By: Relevance
“…We found that this value provides the best agreement between the simulated emitter temperature profile and measurements. Assuming that the heat transfer between these two surfaces is purely radiative and that the radiative flux is close to that of a black body at 1400 (a rough estimation of the emitter temperature [2]), we obtain that should be on the order of 600 . .…”
Section: Thermal Domain and Boundary Conditionsmentioning
confidence: 96%
See 3 more Smart Citations
“…We found that this value provides the best agreement between the simulated emitter temperature profile and measurements. Assuming that the heat transfer between these two surfaces is purely radiative and that the radiative flux is close to that of a black body at 1400 (a rough estimation of the emitter temperature [2]), we obtain that should be on the order of 600 . .…”
Section: Thermal Domain and Boundary Conditionsmentioning
confidence: 96%
“…All information given here about the thermal design of the cathode have been either obtained from the literature on general hollow cathode design [29] or from articles which did specifically focus on the NASA NSTAR cathode [2]. Missing dimensions and parameters were deduced through fitting of numerical simulation results to experimental data obtained for the same NASA NSTAR cathode.…”
Section: Thermal Domain and Boundary Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…[7][8][9][10][11][12] This can estimate energy fluxes on the walls, and then those are utilized as boundary conditions for thermal analysis. 13) Another fluid simulation code has also been developed at University of Toulouse, where a thermal model is self-consistently coupled with plasma simulation. 14) In this study, the hollow cathode plasma was simulated by using a hybrid particle-in-cell (PIC) model that treats the heavy species (neutrals and ions) and electrons as particles and fluid, respectively.…”
Section: Introductionmentioning
confidence: 99%